Dynamical characterization of two differentially disease associated MHC class I proteins in complex with viral and self-peptides. - Narzi, Daniele; Becker, Caroline; Fiorillo, Maria Teresa; Uchanska-Ziegler, Barbara; Ziegler, Andreas; Böckmann, Rainer (Journal of Molecular Biology, 2012)
Major histocompatibility complex (MHC) class I proteins are expressed on the cell surface where they present foreign and self-peptides to effector cells of the immune system. While an understanding of the structural prerequisites for antigen presentation has already been achieved, insight into subtype- or peptide-dependent dynamical characteristics of a peptide-MHC antigen is so far largely obscure. We approached this problem by employing 400-ns molecular dynamics simulations with two human MHC class I subtypes as model systems: the ankylosing spondylitis-associated HLA-B∗27:05 and the non-ankylosing spondylitis-associated HLA-B∗27:09. Both proteins differ only by a micropolymorphism at the floor of the peptide binding groove (Asp116His). A viral (pLMP2) and three self-peptides (pVIPR, pGR, and TIS) were evaluated. The stability of the binding grooves was found to be both subtype dependent and peptide dependent. A detachment from the C- and/or N-terminal pockets was observed for all peptides except TIS, resulting in a stabilization of the α1-helix in both TIS-displaying subtypes. Estimates of the entropy associated with the bound peptides showed an increased entropy for pLMP2 presented by B∗27:05 as compared to B∗27:09, in contrast to the self-peptides. Additionally, the flexibility of the α1-helix that is probably important for receptor binding to the B27:peptide epitope is significantly enhanced for B∗27:05. These in silico results show that the dynamic properties of peptide-MHC complexes are affected both by the bound peptide and by micropolymorphisms of the heavy chain. Our findings suggest a role for the conformational flexibility of MHC class I molecules in the context of recognition by receptors on effector cells.

Evidence for proton shuffling in a thioredoxin-like protein during catalysis. - Narzi, Daniele; Siu, Shirley Weng In; Stirnimann, Christian U.; Grimshaw, John P. A.; Glockshuber, Rudi; Capitani, Guido; Böckmann, Rainer (Journal of Molecular Biology, 2008)
Proteins of the thioredoxin (Trx) superfamily catalyze disulfide-bond formation, reduction and isomerization in substrate proteins both in prokaryotic and in eukaryotic cells. All members of the Trx family with thiol-disulfide oxidoreductase activity contain the characteristic Cys-X-X-Cys motif in their active site. Here, using Poisson-Boltzmann-based protonation-state calculations based on 100-ns molecular dynamics simulations, we investigate the catalytic mechanism of DsbL, the most oxidizing Trx-like protein known to date. We observed several correlated transitions in the protonation states of the buried active-site cysteine and a neighboring lysine coupled to the exposure of the active-site thiolate. These results support the view of an internal proton shuffling mechanism during oxidation crucial for the uptake of two electrons from the substrate protein. Intramolecular disulfide-bond formation is probably steered by the conformational switch facilitating interaction with the active-site thiolate. A consistent catalytic mechanism for DsbL, probably conferrable to other proteins of the same class, is presented. Our results suggest a functional role of hydration entropy of active-site groups.

HLA-B27 subtypes differentially associated with disease exhibit conformational differences in solution. - Febian, Heinz; Huser, Hans; Narzi, Daniele; Misselwitz, Rolf; Loll, Bernhard; Ziegler, Andreas; Böckmann, Rainer; Uchanska-Ziegler, Barbara; Naumann, Dieter (Journal of Molecular Biology, 2008)
Human leukocyte antigen (HLA) class I molecules consist of a heavy chain, beta(2)-microglobulin, and a peptide that are noncovalently bound. Certain HLA-B27 subtypes are associated with ankylosing spondylitis (such as HLA-B*2705), whereas others (such as HLA-B*2709) are not. Both differ in only one residue (Asp116 and His116, respectively) in the F pocket that accommodates the peptide C-terminus. An isotope-edited IR spectroscopy study of these HLA-B27 subtypes complexed with the self-peptide RRKWRRWHL was carried out, revealing that the heavy chain is more flexible in the HLA-B*2705 than in the HLA-B*2709 subtype. In agreement with these experimental data, molecular dynamics simulations showed an increased flexibility of the HLA-B*2705 binding groove in comparison with that of the HLA-B*2709 subtype. This difference correlates with an opening of the HLA-B*2705 binding groove, accompanied by a partial detachment of the C-terminal peptide anchor. These combined results demonstrate how the deeply embedded polymorphic heavy-chain residue 116 influences the flexibility of the peptide binding groove in a subtype-dependent manner, a feature that could also influence the recognition of the HLA-B27 complexes by effector cells.

Interaction pattern of Arg 62 in the A-pocket of differentially disease-associated HLA-B27 subtypes suggests distinct TCR binding modes. - Nurzia, Elisa; Narzi, Daniele; Cauli, Alberto; Mathieu, Alessandro; Tedeschi, Valentina; Caristi, Silvana; Sorrentino, Rosa; Böckmann, Rainer; Fiorillo, Maria Teresa (PLoS ONE, 2012)
The single amino acid replacement Asp116His distinguishes the two subtypes HLA-B*2705 and HLA-B*2709 which are, respectively, associated and non-associated with Ankylosing Spondylitis, an autoimmune chronic inflammatory disease. The reason for this differential association is so far poorly understood and might be related to subtype-specific HLA:peptide conformations as well as to subtype/peptide-dependent dynamical properties on the nanoscale. Here, we combine functional experiments with extensive molecular dynamics simulations to investigate the molecular dynamics and function of the conserved Arg62 of the α1-helix for both B27 subtypes in complex with the self-peptides pVIPR (RRKWRRWHL) and TIS (RRLPIFSRL), and the viral peptides pLMP2 (RRRWRRLTV) and NPflu (SRYWAIRTR). Simulations of HLA:peptide systems suggest that peptide-stabilizing interactions of the Arg62 residue observed in crystal structures are metastable for both B27 subtypes under physiological conditions, rendering this arginine solvent-exposed and, probably, a key residue for TCR interaction more than peptide-binding. This view is supported by functional experiments with conservative (R62K) and non-conservative (R62A) B*2705 and B*2709 mutants that showed an overall reduction in their capability to present peptides to CD8+ T cells. Moreover, major subtype-dependent differences in the peptide recognition suggest distinct TCR binding modes for the B*2705 versus the B*2709 subtype.

Membrane-proximal tryptophans of synaptobrevin II stabilize priming of secretory vesicles. - Borisovska, Maria; Schwarz, Yvonne N.; Dhara, Madhurima; Yarzagaray, Antonio; Hugo, Sandra; Narzi, Daniele; Siu, Shirley Weng In; Kesavan, Jaideep; Mohrmann, Ralf; Böckmann, Rainer; Bruns, Dieter (The Journal of Neuroscience, 2012)
Trans-soluble N-ethylmaleimide-sensitive factor attachment protein (SNAP) receptor (SNARE) complexes formed between the SNARE motifs of synaptobrevin II, SNAP-25, and syntaxin play an essential role in Ca(2+)-regulated exocytosis. Apart from the well studied interactions of the SNARE domains, little is known about the functional relevance of other evolutionarily conserved structures in the SNARE proteins. Here, we show that substitution of two highly conserved tryptophan residues within the juxtamembrane domain (JMD) of the vesicular SNARE Synaptobrevin II (SybII) profoundly impairs priming of granules in mouse chromaffin cells without altering catecholamine release from single vesicles. Using molecular dynamic simulations of membrane-embedded SybII, we show that Trp residues of the JMD influence the electrostatic surface potential by controlling the position of neighboring lysine and arginine residues at the membrane-water interface. Our observations indicate a decisive role of the tryptophan moiety of SybII in keeping the vesicles in the release-ready state and support a model wherein tryptophan-mediated protein-lipid interactions assist in bridging the apposing membranes before fusion.

Molecular determinants of major histocompatibility complex class I complex stability: shaping antigenic features through short and long range electrostatic interactions. - Narzi, Daniele; Winkler, Kathrin; Saidowsky, Juergen; Misselwitz, Rolf; Ziegler, Andreas; Böckmann, Rainer; Alexiev, Ulrike (Journal of Biological Chemistry, 2008)
A single amino acid exchange between the major histocompatibility complex molecules HLA-B(*)2705 and HLA-B(*)2709 (Asp-116/His) is responsible for the emergence of distinct HLA-B27-restricted T cell repertoires in individuals harboring either of these two subtypes and could correlate with their differential association with the autoimmune disease ankylosing spondylitis. By using fluorescence depolarization and pK(a) calculations, we investigated to what extent electrostatic interactions contribute to shape antigenic differences between these HLA molecules complexed with viral, self, and non-natural peptide ligands. In addition to the established main anchor of peptides binding to HLA-B27, arginine at position 2 (pArg-2), and the secondary anchors at the peptide termini, at least two further determinants contribute to stable peptide accommodation. 1) The interaction of Asp-116 with arginine at peptide position 5, as found in pLMP2 (RRRWRRLTV; viral) and pVIPR (RRKWRRWHL; self), and with lysine in pOmega, as found in gag (KRWIILGLNK; viral), additionally stabilizes the B(*)2705 complexes by approximately 5 and approximately 27 kJ/mol, respectively, in comparison with B(*)2709. 2) The protonation state of the key residues Glu-45 and Glu-63 in the B-pocket, which accommodates pArg-2, affects peptide binding strength in a peptide- and subtype-dependent manner. In B(*)2705/pLMP2, protonation of Glu-45/Glu-63 reduces the interaction energy of pArg-2 by approximately 24 kJ/mol as compared with B(*)2705/pVIPR. B(*)2705/pVIPR is stabilized by a deprotonated Glu-45/Glu-63 pair, evoked by allosteric interactions with pHis-8. The mutual electrostatic interactions of peptide and HLA molecule, including peptide- and subtype-dependent protonation of key residues, modulate complex stability and antigenic features of the respective HLA-B27 subtype.